Transient modelling of double-pumped phase conjugation in inverted Nd:YAG - Udaiyan, D; Syed, KS; Green, RPM; Kim, DH; Damzen, MJ (ELSEVIER SCIENCE BV, 1997)
Transient modelling of double-pumped phase conjugation (DPPC) in gain media is presented. Numerical results for reflectivity, diffraction efficiency and temporal behaviour of an injected DPPC system and self-starting DPPC laser are discussed. An experimental gain DPPC system and self-starting version are then modelled, and a comparison is made between numerical and experimental results.